Location, Isolation, and Identification of Mesenchymal Stem Cells from Adult Human Sweat Glands - Yingzhi Ma; Meirong Li; Jinyu Liu; Chuanchao Pang; Jianqing Zhang; Yulin Li; Xiaobing Fu (Hindawi Limited, 2018)
Sweat glands (SGs) are spread over almost the entire surface of the human body and are essential for thermoregulation. Theoretically, tissue-specific stem cells (TSSCs) are excellent candidate cells for the regeneration of SGs due to their genetic stability and differentiation ability. Herein, we attempted to isolate TSSCs derived from adult human sweat glands (ahSGs). ahSGs were localized and identified by H&E staining, double immunofluorescence staining, transmission electron microscope (TEM), and immuno-TEM. We found a population of cells with stem cell characteristics (SGSCs), located in basal myoepithelial cells of the secretory portion of the solenoid bulb. The SGSCs expressed alpha-smooth muscle actin (α-SMA) and showed the typical characteristics of mesenchymal stem cells (MSCs), with a positive antigen profile for CD44, CD73, CD90, and CD105, and had the multilineage differentiation potential to osteoblasts and adipocytes. In addition, the isolated α-SMA positive cells remained stably phenotypic and proliferative cycles at passage 12. This is the first report of successful isolation of MSC-like cells from ahSGs, which may contribute to wound repair and SG regeneration.